Assistance using mobile learning applications to improve skills physical education teacher in the 4.0 era - Aryanti, Silvi; hartati, Hartati; destriana, Destriana; Victorian, Ahmad Richard; Setiyo, Edi; Nanda, Fitri Agung; destriani, Destriani; Azhar, Samsul; Motik, Dewi (Universitas Suryakancana, 2023)
The aim of this research is to evaluate the effectiveness of support in the utilization of mobile learning applications among 38 Physical Education, Sports, and Health Teachers in Lahat Regency. Employing a quantitative descriptive methodology through a survey approach, the research encompasses pre-test and post-test assessments. During the pre-test phase, the results highlight a deficiency in teachers' knowledge regarding mobile learning applications, specifically in comprehending their purpose and operational functionalities. Nonetheless, the post-test outcomes signify a significant enhancement, revealing that the teachers developed awareness and proficiency in utilizing mobile learning applications. They demonstrated an improved understanding of the applications' objectives and acquired the necessary skills for their effective implementation. The transition from the pre-test to the post-test phase signifies the success of the provided assistance in bridging the knowledge gap among the teachers. This implies that the intervention, likely delivered in the form of training or guidance, positively influenced the participants' comprehension and utilization of mobile learning applications. The research findings underscore the critical role of targeted support in augmenting educators' familiarity with technology, ultimately contributing to the seamless integration of mobile learning tools in educational settings. Consequently, this study makes a noteworthy contribution to the ongoing discourse on the significance of mobile applications in pedagogy, particularly within the domain of Physical Education, Sports, and Health.Key words: mobile learning, physical education, era 4.0.